2006
DOI: 10.1002/jnr.21155
|View full text |Cite
|
Sign up to set email alerts
|

Methimazole‐induced cell death in rat olfactory receptor neurons occurs via apoptosis triggered through mitochondrial cytochrome c‐mediated caspase‐3 activation pathway

Abstract: The administration of methimazole is known to induce cell death in rat olfactory receptor neurons (ORNs). We investigated whether this injury occurs via apoptosis or through necrosis and whether it involves the extrinsic or intrinsic pathway. Rats were intraperitoneally injected with vehicle (control) or 300 mg/kg methimazole. The experimental animals were also administered vehicle or a caspase-3 or caspase-9 inhibitor 30 min earlier. The administration of methimazole induced cell death predominantly in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…Some patients could have actually become hypothyroid, but in some patients no other symptoms of hypothyroidism were noted and the symptoms did not reappear during thyroidectomy-induced hypothyroidism (110). A histological examination showing destruction of the olfactory epithelium, sparing the basal cells already after 32 hours of methimazol administration to rats further substantiates the possibility of toxic effects of antithyroid medication (115), which lead to apoptosis of rat olfactory receptor neurons (116). However, in studies of methimazol toxicology effects of hypothyroidism should be carefully excluded.…”
Section: Perception Of Smellsmentioning
confidence: 80%
“…Some patients could have actually become hypothyroid, but in some patients no other symptoms of hypothyroidism were noted and the symptoms did not reappear during thyroidectomy-induced hypothyroidism (110). A histological examination showing destruction of the olfactory epithelium, sparing the basal cells already after 32 hours of methimazol administration to rats further substantiates the possibility of toxic effects of antithyroid medication (115), which lead to apoptosis of rat olfactory receptor neurons (116). However, in studies of methimazol toxicology effects of hypothyroidism should be carefully excluded.…”
Section: Perception Of Smellsmentioning
confidence: 80%
“…In order to investigate whether damage to the nasal epithelium can accelerate prion shedding from the nasal cavity, we induced apoptosis of ORNs in an animal model in which a preexisting prion infection had been established in the OSE. To induce damage to the OSE, hamsters were intraperitoneally inoculated with methimazole, a drug used for treatment of thyroid disorders that also can cause hyposmia, anosmia, and morphological changes to the nasal mucosa (26,51). Methimazole is metabolized by a cytochrome P450-dependent pathway in duct cells of Bowman's gland, which are located in the subepithelial layer of the nasal mucosa, and leads to the induction of apoptosis in olfactory neurons and detachment of the nasal epithelium (6,51).…”
Section: Resultsmentioning
confidence: 99%
“…To induce damage to the OSE, hamsters were intraperitoneally inoculated with methimazole, a drug used for treatment of thyroid disorders that also can cause hyposmia, anosmia, and morphological changes to the nasal mucosa (26,51). Methimazole is metabolized by a cytochrome P450-dependent pathway in duct cells of Bowman's gland, which are located in the subepithelial layer of the nasal mucosa, and leads to the induction of apoptosis in olfactory neurons and detachment of the nasal epithelium (6,51). In the absence of methimazole treatment, the OSE remained intact and prominent immunostaining for OMP, a protein expressed in ORNs, was observed in ORNs in the OSE and in the nerve bundles of ORNs in the subepithelial layer ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19 Previous studies mention the role of mitochondrial dysfunction in thioamide-based drugs toxicity. 20,21 PTU is a thionamide antithyroid drug. Previously, we also found that methimazole as another thionamide antithyroid drug caused mitochondrial injury in isolated rat hepatocytes.…”
Section: Introductionmentioning
confidence: 99%